PENGARUH KEPEMIMPINAN DAN SUPERVISI KEPALA SEKOLAH TERHADAP DISIPLIN KERJA GURU SD SE KECAMATAN BANYUPUTIH KABUPATEN BATANG - Muhammad Zuhri; Titik Haryanti; Yovitha Yuliejatiningsih (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2023)
ABSTRACT The formulation of the problem in this study are: 1) is there any influence of principal's leadership on the quality of graduates in Elementary Schools in Reban District, Batang Regency?, 2) Is there an influence of teacher competence on the quality of graduates in Elementary Schools of Reban District, Batang Regency?, 3) Is there any influence of principal's leadership school and teacher competence together on the quality of graduates in the Reban District Elementary School, Batang Regency?. This type of research is descriptive correlation study or descriptive association study, which is to examine the relationship between two things, two or more variables. The population in this study were all elementary school teachers in Reban District as many as 249 people. With a research sample of 153 people using a simple random sampling technique with the Slovin formula. The data collection method used is the questionnaire method. Analysis of the data used descriptive analysis, test requirements and hypothesis testing which includes simple linear regression analysis and multiple regression analysis. To analyze the data, the SPSS for windows version 25 program was used. The results of this study are: 1) Principal leadership has a strong influence on the quality of graduates (Y) in elementary school teachers throughout Reban sub-district with a value of 64.6%, 2) Teacher competence has a moderate effect on the quality of graduates (Y) in elementary school teachers throughout Reban sub-district with a score of 63.6%, 3) Principal leadership and teacher competence have a strong influence on the quality of graduates (Y) in elementary school teachers in Reban sub-district with a value of 74%. Suggestions in this research are the principal should be able to provide encouragement to all school members by providing advice and improving the work competence of teachers so as to improve the quality of graduates. Keywords: principal leadership, teacher competence, and quality of graduates